Exploring of utility factors that affect intention to use, satisfaction and loyalty in B2C/P2P car-sharing economy - LEE, Sunme (KDI School, 2015)
The Sharing economy has been disseminating and disrupting traditional industries across the world. Although the sharing economy is still fledgling, relatively little comprehensive research has been carried out on the sharing economy. Applying an extended utility model modified from the previous studies, this research investigates the relationships of the types of utilities affecting satisfaction and loyalty as well as a willingness to use the service in the two studies. Study 1 examines the effects of the level of utility related to the levels of satisfaction and loyalty to existing users and intentions to use and expected satisfaction to potential users of B2C car-sharing service and study 2 analyzes the effects of their intension and levels of expected satisfaction to potential users to the P2P car-sharing service. Factor Analysis, regression analysis, ANOVA are applied to examine relationships. The results revealed that the effect of perceived utilities differs between user satisfaction and overall potential users for car-sharing economy; and the effect of perceived utilities differs between B2C and P2P car-sharing economy and some common factors affect both users/non-users and B2C/P2P car-sharing economy. Finally, the findings of this study provided managerial and policy implications not only for sharing economy service startups but also for traditional industry companies and theoretical implications to academia.
Thesis(Master) --KDI School:Master of Public Policy,2015